Inflation Dynamics and Monetary Transmission in Turkey in the Inflation Targeting Regime - Tay Bayramoglu, Arzu; Allen, Larry (Journal of Reviews on Global Economics, 2017)
This study aims to analyse the determinants of inflation and the effectiveness of the monetary transmission in Turkey. The study is covering the period 2003:Q2-2015:Q3 which consists of just an inflation targeting time before 2008, and inflation and financial stability targeting time after 2008 global financial crises. The autoregressive distributed lag model (ARDL) bound test is used for the long-run relationship and a VAR analysis for the short-run dynamics. The cointegration results reveal that the credit growth, US/TL exchange rate, real effective exchange rate, interest rate, and imported inflation are the determinants of inflation in Turkey in the long run. Also, our empirical findings indicate that exchange rate is the most effective factor in inflation. According to the VAR model’s impulse responses, the key drivers of inflation are the movements in the US/TL nominal effective exchange rate, real effective exchange rate, interest rate, GDP growth in the short-term, and credit growth is in the medium-term. ARDL cointegration and impulse responses also show that interest rate and credit growth are efficient instruments as a monetary policy for the inflation targeting and financial stability.